La poésie à l’épreuve de l’histoire - Maryse Staiber (Recherches Germaniques)
During the war years 1915-1918, in which René Schickele was the editor of the pacifist journal Die Weißen Blätter, the literary productivity of the Alsatian author considerably decreases. Nevertheless Schickele publishes in Die Weißen Blätter two important cycles of poems, Gebete (1916) and Zeitsprüche (1918-1919). The present article is dedicated to the second cycle, its poetic structure and function, in particular the famous pacifist poem Abschwur, one of the highlights of Expressionist poetry. The analyses also brings into question the situation, limits and significance of poetry in times of war.